A Model for Measuring the Impact of Broadband Internet on Innovations at Institutions of Higher Learning in Kenya - Muchiri, Rajab Philip (TexilaJournal, 2016)
Objective: The aim of this study is to develop a model for measuring the impact of broadband on innovations at the institutions of higher learning in Kenya. Background: Universities in Kenya are investing huge amounts of money on the provision of Broadband internet. However, the extent to which broadband is being utilised in these institutions to spur innovation is not certain. There is need therefore to measure the extend at which broadband internet influences innovations in these institutions in order to assess value for broadband investment. Methods: The study adopts Porter's Diamond Model to develop the model. The model has four analytical dimensions that form the basis of designing the instruments of data collection. A descriptive study is adopted for the research. Data was collected from existing records, literature review and through interviews. A five-point Likert scale was designed and employed to assess the characteristics and behaviour of broadband consumer responses. Statistical methods were used to test the internal consistency reliability and construct validity of the study variables. Results: The reliability and validity of the measures and measurement instruments were above the recommended level of 0.70 as an indicator of internal consistency. Conclusion: Analysis of the structural model showed that the model performed well and was adequate for the study. Since this was a pilot study and the amount of data used was small, a more comprehensive study that incorporates all the 67 universities in Kenya is recommended.
Keywords: Broadband; Innovations; Internet; Education; Metrics; Model